Rotary kiln and batch pyrolysis of waste tire to produce gasoline and diesel like fuels - Ayanoğlu, Abdulkadir; Yumrutaş, Recep (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this study, waste tire is pyrolyzed in a rotary kiln reactor to obtain more gas, light liquid, heavy liquid, wax products, and less carbon black at their maximum yields as, 20%, 12%, 25%, 8% and 35% of the total weight (4 tones), respectively. Then, the heavy and light oils are reacted with additives such as natural zeolite (NZ) and lime (CaO) at different mass ratio as 2, 6, and 10 wt%, respectively, in the batch reactor to produce liquids similar to standard petroleum fuels. The heavy and light oils mixture samples are distillated to observe their optimum graphics which are similar to gasoline and diesel like fuel. Consequently, the best results are obtained from the CaO sample with 10 wt% in comparison to the ones from the gasoline and diesel fuels. The 10 wt% CaO light liquid mixture resembles to gasoline named as gasoline like fuel (GLF) and the 10 wt% CaO heavy liquid mixture is similar to diesel called as diesel like fuel (DLF). The chemical and physical features of the waste tire, light oil, heavy oil, GLF, and DLF are analyzed by TG (thermogravimetric)/dTG (derivative thermogravimetric), proximate, ultimate, higher heating value (HHV), fourier transform-infrared spectroscopy (FT-IR), Brunauer-Emmett-Teller (BET), sulfur, density, viscosity, gas chromatography-mass spectroscopy (GC-MS), flash point, moisture, and distillation tests. The test results are turned out to be very close to the standard petroleum fuel. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Waste tire; Waste tire oil; Rotary kiln and batch reactors; Pyrolysis; Lime and natural zeolite